Estrategia educativa sobre salud sexual y reproductiva en estudiantes de Tercero de Bachillerato en la Unidad Educativa Fiscomisional Daniel Álvarez Burneo - Poma Aguilar, Edhyra Alejandra (2024)
Sexuality plays a key role along with reproductive health, the latter highlighting the enjoyment of a satisfactory sexual life without the risks of procreating, and with the freedom to decide to do so or not. Studies in Latin America demonstrate the lack of knowledge in sexual and reproductive health among adolescents; however, many of them begin their sexual activity at an early age. This study had as objectives the sociodemographic characterization of the Third Year Baccalaureate students of the Daniel Álvarez Burneo Fiscomisional Educational Unit, the identification of the level of knowledge about sexual and reproductive health and the design of an educational strategy during the academic period October 2022 - March 2023. For this, a quantitative, descriptive, cross-sectional research was developed, a survey was applied that collected sociodemographic information and another on the level of knowledge in sexual and reproductive health along with a test to measure sexual attitudes. 292 students participated, 56.5% were female, 90.1% were between 16 and 17 years old, 98.6% were mixed race, 26% were sexually active, 16.1% started their sexual life at 15 years old, 1% are homosexual; 87.3% have high knowledge about sexual and reproductive health and 95.9% have a favorable attitude about sexuality. Despite there being a high level of knowledge about sexual and reproductive health, adolescents need to have reliable and accessible sources that allow them to consolidate their prior knowledge not only at home but at an institutional level, through the use of educational strategies